Travel motivations and travel careers of Malaysian backpackers - Abdul Latif, Samshul Amry; Saad, Mazni; Ismail, Nuraini; Matniyozov, Murodjon; Fairuz Ramli, Mona (IGI Global, 2022)
The study’s two primary goals are to determine the main travel motives of Malaysian backpackers and to examine the variations in travel motivations across three categories of backpackers: first-time, repeat, and serial. The results were collected using a self-administered online survey adopting a convenience sample technique. The non-normally distributed data were examined using exploratory factor analysis, median score assessment, and Kruskal-Wallis H tests on a sample of 249. Stimulation is the most crucial factor motivating backpackers, while recognition is the least important. The study also found that backpackers’ motivation varied with travel experience. Due to limited research on Asian motivational travel determinants, notably among Malaysian backpackers, this study’s motivational features are drawn from other countries. Future research should focus on non-Western motivators impacting backpackers. There is a need for more research on Asian tourism, notably Malaysian backpackers at various stages of their travel careers.